Assessment of intraoperative fluid misdirection syndrome risk factors according to anatomical and topographical features of anterior segment - I.S. Rebrikov; E.V. Egorova; A.S. Rebrikova; A.V. Lizunov; E.M. Titarenko (Офтальмохирургия)
Relevance. Despite continuous improvement in cataract surgery technology, intraoperative fluid misdirection syndrome remains an underestimated problem. Purpose. To evaluate intraoperative fluid misdirection syndrome clinical manifestation in patients with pseudoexfoliation syndrome (PXS) and without it; to assess intraoperative fluid misdirection syndrome risk factors according to anatomical and topographical features of anterior segment. Material and methods. There were two groups of patients who underwent phacoemulsification in the prospective study. Study group (50 eyes) included patients with complicated cataract, PXS and drug-induced mydriasis less than 6 mm. Control group (50 eyes) included patients with senile cataract, no PXS and drug-induced mydriasis more than 6 mm were enrolled in the control group. Clinical examination of patients included optical biometry, pupillometry using rotational Scheimpflug imaging, ultrasound biomicroscopy for evaluation of iris thickness and sectional area of posterior chamber under drug-induced mydriasis. Results. The average pupil diameter in 1 hour after instillation of mydriatics was 5.46±0.46 mm in the study group and 6.6±0.43 mm in the control group. The sectional area of posterior chamber was 0.67±0.28 mm2 and iris thickness – 0.53±0.05 mm in the study group. The sectional area of posterior chamber was 0.43±0.15 mm2 and iris thickness – 0.64±0.07 mm in the control group. The results revealed positive correlation between pupil diameter and iris thickness, and negative correlation between pupil diameter, iris thickness and sectional area of posterior chamber. Lens floaters were determined after phacoemulsification in 9 eyes (18%) in the study group and in 3 eyes (6%) in the control group. The results showed statistically significant difference between groups (p≤0.05). Conclusion. Lens floaters in the retrolental space as one of the main manifestations of the intraoperative fluid misdirection syndrome were observed in 18% patients of study group and in 6% patients of control group (p≤0.05). Combination of PXS and drug-induced mydriasis less than 6 mm is considered to be the predictive factor of intraoperative fluid misdirection syndrome.